Ketersediaan Cd, Gejala Toksisitas dan Pertumbuhan 3 Spesies Brassicaceae pada Media Gambut yang Dikontaminasi Kadmium (Cd) - Rini Susana; Denah Suswati (Fakultas Pertanian Universitas Tanjungpura, 2011)
Cadmium is a heavy metal and non-essential element but easily absorbed by plants and transferred to the shoots. Cadmium accumulation in various plant species showed varying responses. This research aimed to study the availability of Cd, the toxicity symptoms and growth of three species of Brassicaceae (Brassica rapa var. parachinensis, Brassica rapa var. pekinensis, Brassica oleracea var. alboglabra) on Cd-contaminated peat soil. Contaminant Cd and soil were mixed in different dosages i.e. 2 mgkg-1 Cd, 4 mgkg-1 Cd, 8 mgkg-1 Cd, 16 mgkg-1 Cd and 32 mgkg-1 Cd and used to fill growth pot (5kg/pot). The results showed that the addition of Cd contaminant produces Exchangable-Cd in growth media on range 0.1477 mgkg-1 up to 2.8459 mgkg-1 and influenced fresh weight of shoot of crops used except Brassica oleracea var. alboglabra. Brassica oleracea var. alboglabra showed more tolerant to high Cd exposure, no symptoms of toxicity found so far, while Brassica rapa var. parachinensis and Brassica rapa var. pekinensis showed stunting and chlorosis symptoms as excess of Cd in growth media